2020
DOI: 10.1001/jamanetworkopen.2020.30072
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Time-to-Treatment Initiation and Survival in a Cohort of Patients With Common Cancers

Abstract: Key Points Question What is the association between delays in treatment initiation for common cancers, as are necessary in resource-limited settings and pandemic conditions, with mortality? Findings In this cohort study including 2 241 706 patients with breast, prostate, non-small cell lung, and colon cancer, generally higher all-cause mortality was associated with increasing time to treatment, although the degree varied by cancer type and stage. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
115
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 45 publications
4
115
2
2
Order By: Relevance
“… 27 Finally, a study found a significant association between delays in treatment initiation and 5‐year mortality for the four most common types of cancer in the USA. 28 The drop in cancer care delivery highlighted by our study will likely have similar implications for cancer patients in our network. Quantifying the effect of care delays will be important for better systemwide resource allocation and planning.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 27 Finally, a study found a significant association between delays in treatment initiation and 5‐year mortality for the four most common types of cancer in the USA. 28 The drop in cancer care delivery highlighted by our study will likely have similar implications for cancer patients in our network. Quantifying the effect of care delays will be important for better systemwide resource allocation and planning.…”
Section: Discussionmentioning
confidence: 72%
“…A UK‐based analysis estimated increases in death rates by 4%–16% as a result of diagnostic delays, corresponding to more than 3000 excess deaths in 5 years 27 . Finally, a study found a significant association between delays in treatment initiation and 5‐year mortality for the four most common types of cancer in the USA 28 …”
Section: Discussionmentioning
confidence: 99%
“…Data from Johns Hopkins also suggest that a moderate delay may not matter in the long run, even for men with high‐risk disease 48 . In contrast, some registry data suggest that delays of 3 months or more may be associated with worsened survival in intermediate prostate cancer 49 . We explored this by increasing the definition of definitive treatment to 180 days in our sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Using currently available data 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , the AGO has evaluated the following procedures to reduce false negative rates during the surgical staging of cases who are pN+ CNB before NACT and ycN0 after NACT with AGO + ( Fig. 1 ):…”
Section: Surgical Management Of the Axilla After Neoadjuvant Chemotherapymentioning
confidence: 99%